Identification of Yarrowia lipolytica (Ascomycota: Hemiascomycetes) as a contaminant in obtaining amplified 28S rRNA gene of mollusks - Chirinos, Jenny (2010)
In this paper we identify an unexpected DNA sequence from the amplicons of 28S rRNA gene of terrestrial mollusks. DNA extractions were performed from foot tissues of land snails using a modified CTAB protocol. PCRs were carried out with universal primers for COI gene and oligonucleotides designed for molluscs, for the markers 16S rRNA, 28S rRNA, and ITS-2. Amplified lengths were 706 pb for COI, 330 pb for 16S rRNA, 900 pb for ITS-2, and 583 pb for 28S rRNA. One amplicon of the last marker was of an unexpected length, ~340 pb. DNA sequences were compared in the GenBank database through the BLASTn program and the sample, with the unexpected length, resulted in 100% identity and 99% query coverage with 26S rRNA gene of the yeast Yarrowia lipolytica. Phylogenetic analysis with Neighbour-Joining and the divergence values confirmed the identification, providing results that support the taxonomic placement of the species within the Hemiascomycetes clade.